2018
DOI: 10.1186/s12863-018-0696-6
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of allele-specific expression of genes involved in adipogenesis and lipid metabolism suggests complex regulatory mechanisms of PPARGC1A expression in porcine fat tissues

Abstract: BackgroundThe expression of genes involved in regulating adipogenesis and lipid metabolism may affect economically important fatness traits in pigs. Allele-specific expression (ASE) reflects imbalance between allelic transcript levels and can be used to identify underlying cis-regulatory elements. ASE has not yet been intensively studied in pigs. The aim of this investigation was to analyze the differential allelic expression of four genes, PPARA, PPARG, SREBF1, and PPARGC1A, which are involved in the regulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…The PPARG gene undergoes biallelic expression. Analysis of the allele-specific expression of this gene in porcine fat tissues has shown that both alleles are expressed at similar levels (Stachowiak et al 2018). However, the use of RNA/DNA-FISH allowed us to detect temporal differences in PPARG transcript production.…”
Section: Discussionmentioning
confidence: 99%
“…The PPARG gene undergoes biallelic expression. Analysis of the allele-specific expression of this gene in porcine fat tissues has shown that both alleles are expressed at similar levels (Stachowiak et al 2018). However, the use of RNA/DNA-FISH allowed us to detect temporal differences in PPARG transcript production.…”
Section: Discussionmentioning
confidence: 99%
“…This is the first study that shows differential allelic expression of ACACA , LEP , SCD , and TNF in fat deposits and skeletal muscle of postnatal pigs. The recently reported allelic imbalance of two genes, PPARA and PPARGC1A , out of four analyzed (Stachowiak et al 2018 ) suggests that this phenomenon may be widespread among genes involved in regulating lipid metabolism in pigs. Interestingly, SCD was previously shown as imbalanced in porcine prenatal skeletal muscle, whereas LEP but not FASN , SCD , and TNF displayed differential allelic expression in bovine liver, pituitary, and kidney (Olbromski et al 2013 ; Yang et al 2016 ).…”
Section: Resultsmentioning
confidence: 98%
“…For example, DLK1 was a critical factor in regulating skeletal muscle development and regeneration through Notch dependent 37 . Previous studies found that PPARA was involved in the regulation of fat deposition in porcine subcutaneous fat and longissimus dorsi muscle 38,39 . Besides, myo brillar structural protein myomesin-3 (MYOM3) was not only associated with muscular dystrophy related proteins and muscle strength, which could be a potential biomarker for monitoring of muscular dystrophy, but was hymethylated in ischemic cardiomyopathy 40,41 .…”
Section: Discussionmentioning
confidence: 96%